TRACKING OF MOVING O BJECT IN 3 D (Perner's Contacts, 2012)
The contribution presents the process of two and three dimensional localization of the moving object using a camera system, possible remote data transmission through communication links and image acquisition problems. Moving object recognition is provided by one possible approach - frames difference method, which represents object tracking at any background, image processing was done in MATLAB and the application example is presented by online tracking of moving robot MINDSTORM